The giant South China Mesozoic low-temperature metallogenic domain: Reviews and a new geodynamic model - Hu, Ruizhong; Fu, Shanling; Huang, Yong; Zhou, Mei-Fu; Fu, Shaohong; Zhao, Chenghai; Wang, Yuejun; Bi, Xianwu; Xiao, Jiafei (Journal of Asian earth sciences, 2017)
[Display omitted] •Three low-temperature metallogenic provinces were recognized in LTMD, South China.•The low-temperature deposits in LTMD formed dominantly at 200–230Ma and 130–160Ma.•The formation of LTMD was driven by Indosinian and Yanshanian orogenies.•A new geodynamic model was proposed to explain the formation of the domain. The South China Craton was formed by amalgamation of the Yangtze and Cathaysia Blocks during the Neoproterozoic. During the Mesozoic, voluminous granitic plutons and associated W-Sn polymetallic deposits were formed in the Cathaysia Block. The giant South China low-temperature metallogenic domain (LTMD) includes an area of ∼500,000km2 in the Yangtze Block and is composed of the Chuan-Dian-Qian Pb-Zn, Youjiang Au-As-Sb-Hg and Xiangzhong Sb-Au metallogenic provinces. The Chuan-Dian-Qian Pb-Zn province contains numerous MVT Pb-Zn deposits, whereas the other two provinces are characterized by Carlin-type Au deposits and vein-type Sb, Hg and As deposits. These epigenetic deposits, which formed under low temperature conditions (∼100–250°C), are typically hosted in sedimentary rocks and are locally controlled by faults and fractures. The deposits formed dominantly at 200–230Ma and 130–160Ma, corresponding to Indosinian (Triassic) and Yanshanian (Jurassic to Cretaceous) orogenies, respectively. Indosinian mineralization is recognized in all three provinces, but Yanshanian mineralization occurred only in the Youjiang and Xiangzhong provinces. The Indosinian orogeny, which involved collision of the Indochina Block with the South China Craton, resulted in circulation of basinal brines that leached ore-forming elements from adjacent sedimentary strata to form the Chuan-Dian-Qian Pb-Zn province. Deep-seated granitic magmas generated during this orogeny caused extensive circulation of meteoric water that mobilized ore-forming elements from the sedimentary strata to form the Carlin-type Au deposits in the Youjiang province, and the Sb-Au deposits in the Xiangzhong province. The Indosinian orogeny was the key factor in establishing the metallogenic framework of the LTMD. It produced widespread mineralization in the three metallogenic provinces, each of which has unique features reflecting differences in the nature and composition of the basement rocks. The Yanshanian metallogeny was less important and overprinted the older ore deposits in the Youjiang and Xiangzhong provinces.